An Analysis of Guidance and Counseling Teachers’ Competence in Understanding Non-Cognitive Diagnostic Assessment Instruments in Public Senior High Schools and Vocational Schools in Rembang Regency - Indiyani, Rizki; Utomo, Dian Purbo (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the competence of school counselors in understanding non-cognitive diagnostic assessment instruments. Non-cognitive diagnostic assessments play a crucial role in evaluating students' psychosocial aspects, such as attitudes, motivation, and social skills, which can influence their development and academic performance. This research adopts a quantitative approach with a descriptive design, involving 22 school counselors from public senior high schools and vocational schools in Rembang Regency, selected through purposive sampling. Data were collected using a questionnaire measuring the counselors' understanding of non-cognitive diagnostic assessment instruments and their skills in applying them. The analysis reveals that the competence of school counselors in understanding these non-cognitive diagnostic assessment instruments varies across schools, with the average competence falling within the moderate category (49%). Some schools, such as Vocational School A, demonstrated higher competence, while Senior High School A showed lower understanding. This study recommends the need for continuous training for school counselors to enhance their understanding and application of non-cognitive diagnostic assessments, as well as the importance of school policy support in developing counselors' competencies. These findings contribute to the development of more effective guidance and counseling services that can better support students' psychosocial well-being.